Optimizing Interdepartmental Communication and Information Flow: The Role of Process Control in Production and Management Accounting : Case Study - Tuovinen, Essi (My University, 2025)
In the manufacturing of complex products, the seamless flow of information both within systems and in interdepartmental communication is essential. Gaps in information flow and delayed availability of information can cause challenges in the later stages of cross-functional processes and result in errors. This case study examines the role and importance of the Process Control department, established a few years ago in the case company. In addition to clarifying the role, the aim is to investigate and improve interdepartmental communication, while optimizing cost accuracy and the consistency of maintained data with the production environment. The data maintained by the Process Control interconnects the production process, product structure, and cost information, linking multiple departments. The role of the department is particularly examined between the finance and production functions within the organization, identifying the information needs of different departments and examining current communication practices. The primary data consists of semi-structured interviews and observations, while internal reports and documents represent the secondary data. The data was analyzed with thematic analysis, which identified that the department’s role and significance can be categorized into two main themes. The first theme addresses the creation and maintenance of standard process data, which connects product structure, the production process, and the needs of the finance function for cost management. In situations deviating from the standard process, a second role emerges, in which the department supports cost tracking and aims to ensure the alignment of data with the actual production situation. The findings highlight the importance of effective communication in maintaining data accuracy and preventing information gaps, which requires an understanding of stakeholder information needs. An annual clock of the Process Control is developed, visualizing recurring tasks throughout the year and recommending improvements to interdepartmental communication practices. The research indicates that accurate data and proactive communication are crucial in cross-functional processes in manufacturing complex products.

Monimutkaisten tuotteiden valmistuksessa tiedon sujuva kulkeutuminen niin järjestelmissä kuin osastojen välisessä viestinnässä on tärkeää. Tiedonkulun katkokset ja viivästynyt tiedon saatavuus voivat aiheuttaa haasteita poikkitoiminnallisen prosessin myöhemmissä vaiheissa ja altistaa virheille. Tapaustutkimuksessa tarkastellaan muutamia vuosia sitten tapausyrityksessä perustetun Process Control -osaston roolia ja merkitystä. Tavoitteena on roolin selventämisen lisäksi tutkia ja parantaa osastojen välistä tiedonkulkua, sekä optimoida kustannustarkkuutta ja ylläpidetyn tiedon yhdenmukaisuutta tuotantoympäristön kanssa. Process Controlin ylläpitämä data yhdistää tuotantoprosessin, tuotteen rakenteen ja kustannustiedot yhdistäen useita osastoja. Osaston merkitystä tarkastellaan erityisesti talous- ja tuotantofunktioiden välillä, kartoitetaan eri osastojen tietotarpeita ja tutkitaan nykyisiä viestintäkäytäntöjä. Ensisijainen tutkimusaineisto koostuu puolistrukturoiduista haastatteluista ja havainnoinnista, kun taas toissijaisen aineiston muodostavat sisäiset raportit ja dokumentit. Aineisto analysoitiin temaattisen analyysin avulla, jossa tunnistettiin roolin ja merkityksen jakautuvan kahteen pääteemaan. Ensimmäinen teema liittyy standardiprosessin tietojen luomiseen ja ylläpitoon, jossa yhdistetään tuotteen rakenne, tuotantoympäristön prosessi, sekä talousfunktioiden tarpeet kustannusten seuraamiseen. Standardiprosessista poikkeavissa tilanteissa tulee esille toinen rooli, jossa osasto tukee kustannusten ohjaamista poikkeavissa tilanteissa ja pyrkii varmistamaan järjestelmissä olevan tiedon vastaavuuden tuotannon kanssa. Havainnot korostavat tehokkaan viestinnän merkitystä tiedon tarkkuuden ylläpitämisessä ja tietokatkosten ehkäisemisessä, mikä edellyttää sidosryhmien tietotarpeiden ymmärrystä. Tutkimuksessa kehitetään Process Controlin vuosikello, jossa visualisoidaan vuoden aikana toistuvat työtehtävät ja ehdotetaan parannuksia osastojen välisiin viestintäkäytäntöihin. Tutkimus osoittaa tarkan datan ja ennakoidun viestinnän olevan olennaista poikkitoiminnallisissa prosesseissa monimutkaisessa valmistusympäristössä.
Keywords: fi=Tuotantotalous (tekniikka)|en=Industrial Management and Engineering|; Master's Programme in Industrial Systems Analytics